PENGELOLAAN POTENSI PARIWISATA MENGGUNAKAN PENDEKATAN COMMUNITY BASED TOURISM (CBT) DI DESA BOTUTONUO KECAMATAN KABILA BONE KABUPATEN BONE BOLANGO - Suleman, Syahputra Adisanjaya; Pomalingo, Ipors; Arsyad, Yolandika (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2024)
Bone Bolango Regency is one of 6 districts in Gorontalo Province which has tourism potential in the form of a coastal area directly bordering Tomini Bay. One of the villages that has superior tourism potential in the form of beaches is Botutonuo Village, located in Kabila Bone District, where some people take advantage of this potential as a source of income. Unfortunately, some of the tourism potential is managed by investors, thus there are significant differences between management. For instance, the availability of amenities, investors managed their place with attractive concepts and facilities, while those managed by local communities were still traditional. This means that the benefits of tourism do not raise significant results to the community welfare, because tourists generally prefer the private sector destinations. Ideally, tourism should be managed by the community and the benefits can be distributed to improve the standard living of the community, therefore there is a need for a community-based tourism (CBT) concept. CBT focuses on empowering and developing communities to plan, implement and evaluate the results of managing existing tourism potential. Hence, this research and service is focused on exploring tourism potential and implementing CBT in tourism management in Botutonuo Village through the preparation, realization and evaluation stages by fully involving the community. The result showed the community was able to form a tourism management structure to coordinate some activities, such as preserving the underwater environment through coral reef planting and managing marine waste to make souvenirs from shells.